PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJARAN IPA SISWA KELAS III SEKOLAH DASAR - Gemi Gustiani; Hany Handayani; Atep Lesmana; Annisa Nurfitriani; Ihsan Rizali; Asep Nurhuda; Nafisa Putri Kinastringrum (STKIP Subang, 2023)
Natural science education can be a vehicle for students to learn about themselves and the natural world around them, as well as prospects for further development in applying it in everyday life. However, in fact, currently science learning is a boring lesson for elementary school students, because when science learning takes place, the average teacher only gives theory, so sometimes there are students who don't understand, and when the students don't understand, the students don't understand. dare to ask the teacher. This of course causes problems where it has an impact on student learning outcomes. This study aims to determine the effect of the Discovery Learning learning model on science learning outcomes in class III students at SDN 2 Sindangkasih Purwakarta District, Purwakarta Regency, West Java. This study used a quantitative approach with a quasi-experimental method with the Nonequivalent Control Group Design type. The population in this study were all students of class III SDN 2 Sindangkasih, the samples used in this study were class III A as the experimental class and class III C as the control class. Data collection techniques in this study used tests, questionnaires, observation, and documentation. The results of the research data analysis were preceded by a normality test. The results showed that there was an influence of the discovery learning model on students' science learning outcomes. This is based on the calculation of the Mann-Whitney test with the Asymp Sig value obtained. (2-tailed) of 0.197 ≥ 0.05, then is accepted, and seen from the questionnaire responses of students who achieved a result of 91.9 which is in the very positive category. The results of this study indicate that the use of discovery learning learning models has an influence on the science learning outcomes of elementary school students.